Predictors of timely opioid agonist treatment initiation among veterans with and without HIV. (1st May 2019) - Wyse, Jessica J.; Robbins, Jonathan L.; McGinnis, Kathleen A.; Edelman, E. Jennifer; Gordon, Adam J.; Manhapra, Ajay; Fiellin, David A.; Moore, Brent A.; Korthuis, P. Todd; Gaither, Julie R.; Gordon, Kirsha; Skanderson, Melissa; et al.
Highlights: 4.9% of patients initiated OAT within 30 days of a new OUD episode. Timely OAT less likely among patients with HIV, psychiatric diagnosis, rurality. Timely OAT more likely among African Americans (AFAM), alcohol-related diagnosis, patients with HCV. Abstract: Background: Opioid use disorder (OUD) is prevalent among people with HIV (PWH). Opioid agonist therapy (OAT) is the most effective treatment for OUD and is associated with improved health outcomes, but is often not initiated. To inform clinical practice, we identified factors predictive of OAT initiation among patients with and without HIV. Methods: We identified 19, 698 new clinical encounters of OUD between 2000 and 2012 in the Veterans Aging Cohort Study (VACS), a national observational cohort of PWH and matched uninfected controls. Mixed effects models examined factors predictive of OAT initiation within 30-days of a new OUD clinical encounter. Results: 4.9% of both PWH and uninfected patients initiated OAT within 30 days of a new OUD clinical encounter. In adjusted models, participants with a psychiatric diagnosis (aOR = 0.54, 95% CI 0.47 – 0.62), PWH (aOR = 0.79, 95% CI 0.68–0.92), and rural residence (aOR = 0.56, 95% CI 0.39-0.78) had a lower likelihood of any OAT initiation, while African-American patients (aOR = 1.60, 95% CI 1.34–1.92), those with an alcohol related diagnosis (aOR = 1.76, 95% CI 1.48–2.08), diagnosis year 2005–2008 relative to 2000–2004 (aOR = 1.24, 95% CI 1.05–1.45), and patients with HCV (aOR = 1.50, 95% CI 1.27–1.77) had a greater likelihood of initiating any OAT within 30 days. Predictive factors were similar in the total sample and PWH only models. Conclusions: PWH were less likely to receive timely OAT initiation than demographically similar uninfected patients. Given the health benefits of such treatment, the low rate of OAT initiation warrants focused efforts in both PWH and uninfected populations.